α1‐Antitrypsin and serum albumin mRNA accumulation in normal, acute phase and ZZ human liver - Riley, J.H.; Bathurst, I.C.; Edbrooke, M.R.; Carrell, R.W.; Craig, R.K. (FEBS letters, 1985)
α1‐Antitrypsin and albumin mRNA levels of 4 human livers were assessed using a newly sequenced cDNA clone of the carboxyterminal third of α1‐antitrypsin and a previously cloned albumin cDNA sequence. The relative concentration of α1‐antitrypsin mRNA was the same in poly(A)‐containing RNA isolated from acute phase (MM) and α1‐antitrypsin deficient (ZZ) individuals. In the acute phase liver relative to the normal (MM) liver, total RNA extracts showed a marked decrease in albumin mRNA concentration but no increase in α1‐antitrypsin mRNA. The ZZ liver showed decreased total and poly(A)‐containing RNA content but the same proportion of α‐antitrypsin to albumin mRNA as in the normal (MM) liver. This supports other evidence that ZZ α1‐antitrypsin deficiency is due to a defect in polypeptide processing (secretion) rather than a deficiency in mRNA accumulation.